KEPEMIMPINAN BERBASIS KEARIFAN LOKAL PACU JALUR DALAM MANAJEMEN BERBASIS SEKOLAH DI SMP NEGERI 2 KUANTAN HILIR SEBERANG - Septiani, Diva Erlina; Suryaningsih, Feby; Tani, Diana Olensia; Yanti, Noveri; Ferlinitasari, Novi; Zilviatri, Zilviatri; Marhadi, Hendri; Mustafa, M. Nur (JURNAL TARBIYAH, 2025)
School principal leadership based on local wisdom is a leadership model that integrates local values, norms, traditions, and culture into the management and decision-making processes of schools. This study aims to describe the implementation of Pacu Jalur-based local wisdom leadership in School-Based Management (SBM) and its impact on student character development and the improvement of learning quality at SMP Negeri 2 Kuantan Hilir Seberang. This study uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. The results indicate that Pacu Jalur-based local wisdom leadership is reflected in values such as cooperation, sportsmanship, mutual aid, responsibility, hard work, and discipline. These values are implemented in learning activities, extracurricular programs, and school culture, contributing to the formation of students' character and the creation of a collaborative and disciplined learning environment. The findings show that local wisdom can serve as a legitimate managerial and pedagogical framework, as it is capable of strengthening character education, building a positive school culture, and making the educational process more contextual with the local cultural environment.